Development of Comic-Based Learning Modules to Improve Students' Critical Thinking Skills in Islamic Religious Education and Ethics for Junior High School Students - olivia, olivia; Remiswal, Remiswal; Misra, Misra; Sepriyanti, Nana; Trinova, Zulvia; Batubara, Juliana (Ahlussunnah: Journal of Islamic Education, 2025)
This research is motivated by the low critical thinking skills of seventh-grade students of SMPN 3 Pancung Soal, Pesisir Selatan Regency in the subject of Islamic Religious Education and Character Building. This occurs because the use of conventional learning modules that tend to be monotonous, less visually appealing, and do not encourage students to actively think or discuss. This study aims to develop a comic-based learning module that is valid, practical, and effective in improving students' critical thinking skills. This type of research is research and development (R&D) with the 4D model (Define, Design, Development, Disseminate). The define stage is carried out through observation, interviews, and documentation to identify needs. At the design stage, a comic-based module design is produced. The development stage involves expert validation, practicality testing by teachers and students, and effectiveness testing through critical thinking ability tests with score analysis, Independent Sample T-Test, and N-Gain. The dissemination stage is carried out by distributing the module in printed and PDF forms. The results showed that the validity of the module obtained a percentage of 86% (very valid). Practicality received a score of 90% from teachers and 86% from students (very practical). The effectiveness test showed a significance of 0.000 (<0.05) and an average N-Gain of 77% (high category). Thus, the comic-based learning module was proven valid, practical, and effective in improving students' critical thinking skills.